2013
DOI: 10.1080/00032719.2012.703273
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Multi-Pumping Pulsed Flow System with Spectrophotometric Detection for the Determination of Phosphate in Natural Waters

Abstract: In this work, an automated multipumping pulsed flow system was implemented for the determination of phosphate in natural waters. The developed flow approach was based on the spectrophotometric determination of phosphate by using the vanadomolybdate reaction. The exploitation of a very simple manifold configuration relying on the utilization of just two active components, in this case two solenoid actuated micropumps that were accountable for sample and reagent insertion and commutation, reaction zone formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…When Eu 3 + ions were added, the CdSe QDs tended to aggregate, resulting in the formation of huge complexes ( Figure 1B). However, the aggregates formed are redispersed with the addition of PO 4 3À ions ( Figure 1C), which confirmed that the introduction of PO 4 3À ions disrupted the Eu 3 + induced CdSe QDs aggregations because Eu 3 + ions have a higher affinity for oxygen-donor atoms from PO 4 3À ions. UV-vis and PL spectra were also used to characterize the obtained CdSe QDs, CdSe QDs-Eu 3 + aggregates and CdSe QDs-Eu 3 + /phosphate, respectively.…”
Section: Characterization Of Cdse Qdssupporting
confidence: 75%
See 3 more Smart Citations
“…When Eu 3 + ions were added, the CdSe QDs tended to aggregate, resulting in the formation of huge complexes ( Figure 1B). However, the aggregates formed are redispersed with the addition of PO 4 3À ions ( Figure 1C), which confirmed that the introduction of PO 4 3À ions disrupted the Eu 3 + induced CdSe QDs aggregations because Eu 3 + ions have a higher affinity for oxygen-donor atoms from PO 4 3À ions. UV-vis and PL spectra were also used to characterize the obtained CdSe QDs, CdSe QDs-Eu 3 + aggregates and CdSe QDs-Eu 3 + /phosphate, respectively.…”
Section: Characterization Of Cdse Qdssupporting
confidence: 75%
“…Figure 3B shows the ECL intensity of CdSe QDs at different pH values (4)(5)(6)(7)(8)(9)(10)(11). Experiments show that, with an increasing solution pH from pH 4 to 11, the ECL intensity of the CdSe QDs film gradually increases for the pH 4 to 9 and then decreases with the further increasing pH value.…”
Section: Optimizing Phmentioning
confidence: 92%
See 2 more Smart Citations
“…Besides, some health problems, such as hyperparathyroidism, vitamin D deficiency, and fanconi syndrome, can be diagnosed by measuring phosphate anions concentrations in body fluids 2. Accordingly, considerable detection strategies for phosphate anions and their derivatives have been developed including chromatography, spectrophotometry 3, 4, fluorometry 5–7, electrochemical analysis 8, 9, and enzymatic biosensors 10. However, the drawbacks of most of these techniques are that they often require time‐consuming sample pretreatment procedures, sophisticated instrumentation, large sample volumes, or specialized skills.…”
Section: Introductionmentioning
confidence: 99%